Pragmatic guide to Sass 3 : tame the modern style sheet - Catlin, Hampton; Catlin, Michael Lintorn (Pragmatic programmers., 2016)
Design websites faster than ever using Sass--the most mature and popular CSS meta-language. On any platform, integrate Sass into your project, create a reusable style guide, and use maps to drastically reduce duplication in your stylesheets. You'll see how to code the right way in Sass with short, clear examples on two-page spreads that show the explanation on one side and code examples on the other. This ultimate guide to using Sass, written by its creator, is updated and expanded with all the new features found in Sass 3.4, making you an expert in no time.